2014
DOI: 10.1016/j.jvs.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Use of Disposable Radiation-Absorbing Surgical Drapes Results in Significant Dose Reduction During EVAR Procedures

Abstract: The effect of carotid artery stenting (CAS) and carotid endarterectomy (CEA) on cognitive function is unclear. Both cognitive improvement and decline have been reported after CAS and CEA. We aimed to compare the changes in postprocedural cognitive function after CAS versus CEA. A systematic qualitative review of the literature was conducted according to the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-analysis statement for studies evaluating the changes in cognitive functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…It therefore resulted in an overestimation of their real personal dose. Kloeze et al reported a significant reduction in operator doses during EVAR using disposable radiationabsorbing drapes (Radpad, Worldwide Innovations and Technologies Inc., Kansas City, Missouri) in a non-dedicated angiosuite [12]. Their FO doses obtained in group with shielding drapes are comparable to the EVAR FO doses from our study on a dedicated fluoroscopy system without additional shielding.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It therefore resulted in an overestimation of their real personal dose. Kloeze et al reported a significant reduction in operator doses during EVAR using disposable radiationabsorbing drapes (Radpad, Worldwide Innovations and Technologies Inc., Kansas City, Missouri) in a non-dedicated angiosuite [12]. Their FO doses obtained in group with shielding drapes are comparable to the EVAR FO doses from our study on a dedicated fluoroscopy system without additional shielding.…”
Section: Discussionsupporting
confidence: 74%
“…Recently, work has been published on radiation exposure during endovascular aortic repair procedures [11][12][13]. Besides differences in fluoroscopy units and acquisition parameters, some general comments can be made.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a randomized study by Kloeze et al involving the use of radiation absorbing surgical drapes resulted in a 55% reduction in radiation dose for the interventionalist. 23 However, these methods do not reduce the dose of radiation to the patient, are often made disposable by design, and need to be reinstalled before every procedure. Therefore, lowering the patient entry dose seems more appropriate to reduce radiation exposure to all persons involved.…”
Section: Discussionmentioning
confidence: 99%
“…46 While radiation reducing surgical drapes are now routinely available and have been shown to successfully reduce the radiation exposure of staff, these have been primarily used by radiologists and not adopted by orthopaedic or spinal surgeons. 48 , 49 With the current economic climate stretching resources globally, it is also worth considering the cost of equipment, including drapes. Disposable surgical drapes cost relatively more than reusable drapes and, as our review has not clearly shown benefit over reusable drapes, there remains economic debate over the use of disposable drapes.…”
Section: Discussionmentioning
confidence: 99%